(untitled) (Al-Academy, 2024)
Intertextuality is one of the modern critical concepts. It is a process of intertextual interaction between the works of one artist Or the intertextuality is in the artist’s own works and another in terms of style, method of treatment, and genre. It gives the recipient a major role in interpreting and interpreting the artistic work through cross-referencing and identifying points of intertextuality between the different works. The researcher collected scientific materials in a way that serves The research topic is in four chapters: The first chapter, the methodological framework of the research: to clarify the research problem and the importance of the research, while the research aims to reveal intertextuality and its formal applications in the works of contemporary Iraqi potters, the temporal boundaries that were determined (2020 - 2024), the spatial boundaries of Iraq, and the definition of search terms. Chapter Two: The theoretical framework of the research: The first topic: The concept of intertextuality. The second topic: Intertextuality in art formation, previous studies, and indicators of the theoretical framework. Chapter Three: The procedural framework of the research: The research community, the research sample, and the research tool. The researcher adopted the indicators of the theoretical framework and the research methodology, then analyzed the sample. Chapter Four: The results, including 1 - Ceramic works are produced based on entering into intertextual relationships and with different mechanisms and methods with different references that had previous bad results. His gender or other genders. This is what became clear through the selected samples, as the researcher did not find any work from the samples that was devoid of intertextual references that contributed effectively to its structure, in addition to conclusions, recommendations and proposals